Geração de massa para neutrinos ativos na presença de 1 ou 2 neutrinos estéreis - Machado, A. C. B [UNESP] (2007)
This work presents a study on the changes we have done in the Standard Model (SM), adding mass to neutrinos, in order to observe the alterations these changes may cause to the whole Electroweak Standard Model (ESM). Therefore, the main idea of this study is to get mass matrices by introducing one or two sterile neutrinos in the ESM mater content and mechanisms to generate Majorana mater to ESM' s active neutrinos, such as, radioactive corrections, the dimension ﬁve operator, and the scalar triplet. The ﬁnal models, and therefore the mass matrices, come from the possible combinations between the studied mechanisms